Seronegative and Low Seropositive Treatment-Naive Secondary Syphilis in India: A Cross Sectional Study - Aparajita Ghosh; Saumya Panda; Surjyamukhi Bhattacharyya (Wolters Kluwer Medknow Publications, 2024)
The non-treponemal tests like VDRL and RPR hold an important place in the diagnosis of syphilis. In many countries, these tests are used for screening, with positive results being subsequently confirmed by treponemal or specific tests like TPHA or FTA-ABS. Recent observations of low-titer VDRL or RPR positivity (<1:8) or negative results in patients with clinically active syphilis are becoming a cause for concern especially in the backdrop of a resurgence of the disease. Such a scenario might undermine the usefulness of VDRL or RPR as effective screening test and for treatment monitoring. We studied the titers of non-treponemal serological test (VDRL) in non-HIV-positive, untreated cases of secondary syphilis (diagnosed clinically and confirmed serologically with specific treponemal tests like TPHA or FTA-ABS). It was an OPD-based cross-sectional study, which included patients presenting with muco-cutaneous lesions suggestive of secondary syphilis, confirmed serologically with positive specific treponemal tests, who were seronegative for HIV1 and 2 and had not received treatment with injectable benzathine penicillin. Their VDRL titers were noted. Information regarding duration of lesions and any previous genital ulcer was obtained, and additional information was sought regarding any medications taken during the last two months. Nineteen patients (12 males, 4 females, and 3 transgender individuals) between the ages of 18 and 46 years were included in the study. Ten of these cases (52.63%) had a VDRL titer of less than 1:8 (non-reactive in 5 patients, titer of 1:4 in 5 patients). Among the remaining nine cases, a titer of 1:8 was observed in six, 1: 16 in two, and 1:32 in one case. Our observations raise concerns regarding the possibility that a significant number of patients with active syphilis and potential to transmit the disease are being left untreated because of low or negative titers in the screening tests. This may account for the slow resurgence of syphilis as documented by increase in case rates and incidence of congenital syphilis in different parts of the world.